2021
DOI: 10.1101/2021.11.08.467792
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Context-dependent inversion of the response in a single sensory neuron type reverses olfactory preference behavior

Abstract: The valence and salience of individual odorants are modulated by an animal’s innate preferences, learned associations, and internal state, as well as by the context of odorant presentation. The mechanisms underlying context-dependent flexibility in odor valence are not fully understood. Here we show that the behavioral response of C. elegans to bacterially-produced medium-chain alcohols switches from attraction to avoidance when presented in the background of a subset of additional attractive chemicals. This c… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 106 publications
(143 reference statements)
0
3
0
Order By: Relevance
“…Similar responses have also been observed in the ORNs of aquatic organisms, including lobster ( Bobkov et al, 2012 ), where a subpopulation of lobster ORNs has been shown to rhythmically burst in a fashion essential for determining the edges of a turbulent plume during odor tracking ( Michaelis et al, 2020 ). Recent results in Caenorhabditis elegans show that hedonic changes in olfactory context can change the responses of an ORN ( Khan et al, 2021 ). However, to our knowledge, our results provide the first evidence that ORNs can generate a well-defined set of discrete temporally structured response motifs for different odors.…”
Section: Discussionmentioning
confidence: 99%
“…Similar responses have also been observed in the ORNs of aquatic organisms, including lobster ( Bobkov et al, 2012 ), where a subpopulation of lobster ORNs has been shown to rhythmically burst in a fashion essential for determining the edges of a turbulent plume during odor tracking ( Michaelis et al, 2020 ). Recent results in Caenorhabditis elegans show that hedonic changes in olfactory context can change the responses of an ORN ( Khan et al, 2021 ). However, to our knowledge, our results provide the first evidence that ORNs can generate a well-defined set of discrete temporally structured response motifs for different odors.…”
Section: Discussionmentioning
confidence: 99%
“…The data we present for intraneuronal olfactory discrimination is specific to the particular circumstance in which a saturating concentration of an odorant sensed by one neuron is present along with a lower concentration of a second odorant sensed by the same neuron. While the use of arrestin to desensitize active receptors is presumably relatively generalized across diverse odorants under conditions broadly similar to those we’ve employed, other mechanisms have been recently proposed and likely also play a role ( 23 ).…”
Section: Discussionmentioning
confidence: 84%
“…Similar responses have also been observed in the ORNs of aquatic organisms including lobster (Bobkov et al, 2012), where a subpopulation of lobster ORNs has been shown to rhythmically burst in a fashion essential for determining the edges of a turbulent plume during odor tracking (Michaelis et al, 2020). Recent results in C. elegans show that hedonic changes in olfactory context can change the responses of an olfactory receptor neuron(Khan et al, 2021, Preprint ). However, to our knowledge, our results provide the first evidence that ORNs can generate a well-defined set of discrete temporally structured response motifs for different odors.…”
Section: Discussionmentioning
confidence: 99%